Suitable reference tissues for quantitative susceptibility mapping of the brain - Straub, Sina; Schneider, Till M.; Freitag, Martin T.; Ziener, Christian H.; Schlemmer, Heinz-Peter; Ladd, Mark E.; Laun, Frederik B. (Magnetic resonance in medicine, 2017)
Purpose Since quantitative susceptibility mapping (QSM) quantifies magnetic susceptibility relative to a reference value, a suitable reference tissue has to be available to compare different subjects and stages of disease. Methods To find such a suitable reference tissue for QSM of the brain, melanoma patients with and without brain metastases were measured. Twelve reference regions were chosen and assessed for stability of susceptibility values with respect to multiple intra-individual and inter-individual measurements, age, and stage of disease. Results Cerebrospinal fluid (CSF), the internal capsule and one region in the splenium of the corpus callosum are the regions with the smallest standard deviations of the mean susceptibility value. The mean susceptibility is 0.010 ± 0.014 ppm for CSF in the atrium of the lateral ventricles (csfpost), −0.060 ± 0.019 ppm for the posterior limb of the internal capsule (ci2), and −0.008 ± 0.019 ppm for the splenium of the corpus callosum. csfpost and ci2 show nearly no dependence on age or stage of disease, whereas some other regions, e.g., the red nucleus, show moderate dependence on age or disease. Conclusion The internal capsule and CSF appear to be the most suitable reference regions for QSM of the brain in the melanoma patients studied. Both showed virtually no dependence on age or disease and small variations among patients. Magn Reson Med 78:204-214, 2017. © 2016 International Society for Magnetic Resonance in Medicine
Published online: 16 August 2016
Gesehen am 15.04.2020